1992
DOI: 10.1021/ac00045a011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of redox system structure on electron-transfer kinetics at ordered graphite and glassy carbon electrodes

Abstract: The basal plane of highly ordered pyrolytic graphite (HOPG) serves as an ordered model of more commonly used electrode surfaces such as glassy carbon (GC) and pyrolytic graphite. The defect density on the basal plane HOPG was reduced by careful cleaving and cell design and was verified to be low by requiring that AEp for Fe(CN)6*123"/4" (1 M KCI) be greater than 700 mV for a 0.2 V/s scan rate. Then a variety of redox systems were examined on "validated" HOPG surfaces, and variations In the electron transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
300
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(317 citation statements)
references
References 28 publications
(6 reference statements)
15
300
2
Order By: Relevance
“…The well-known scotch tape method was used to cleave HOPG. 23,[27][28][29]33,41,[45][46][47][48][49] Similarly, the CV response of pBDD was measured either with or without polishing the electrode surface between each CV, and we again state when each method was used. The pBDD electrode was polished with alumina particles (ca.…”
Section: Macroscale Electrochemistrymentioning
confidence: 99%
“…The well-known scotch tape method was used to cleave HOPG. 23,[27][28][29]33,41,[45][46][47][48][49] Similarly, the CV response of pBDD was measured either with or without polishing the electrode surface between each CV, and we again state when each method was used. The pBDD electrode was polished with alumina particles (ca.…”
Section: Macroscale Electrochemistrymentioning
confidence: 99%
“…AM, ZYA, SPI-1 and SPI-3 grade HOPG surfaces were freshly prepared for voltammetry measurements by peeling back the top layers of HOPG with Scotch tape, with the cleaving direction maintained to avoid deformation, until the tape was totally covered with HOPG, as routinely done in the literature. 27,37,40,41,49,50,57,[59][60][61] Fresh surfaces of AM HOPG were also revealed by mechanically cleaving with a clean razor blade, inserted perpendicular to the basal plane with a gentle rocking motion until a small piece delaminated spontaneously, as adopted elsewhere. 27,51,62 Both procedures were used for the macroscopic studies of AM grade HOPG, with samples respectively labelled as AM S and AM M .…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…40,49,50 Moreover, microscopic and nanoscopic measurements have reported high intrinsic activity of the basal surface, 40,41,49,[51][52][53][54][55] in contrast with the earlier literature, which proposed that the basal surface of HOPG was inert or largely inert. 56,57 In this paper we report detailed investigations of the adsorption and electrochemistry of AQDS on HOPG, with the particular goal of elucidating whether it is an appropriate measure for determining step edge density. More generally, this serves as an important model system to introduce new methodology for localized quantitative measurements of adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…McCreery has shown that HOPG electrodes attenuate interfacial ET rates by ca. 3-4 orders of magnitude [19].…”
Section: Resultsmentioning
confidence: 99%